MATHEMATICAL MODEL FOR IDENTIFICATION OF CONSTELLATION OF NAVIGATING SATELLITES GPS, GLONASS, GALILEO - Харченко, В.П.; Кукуш, О.Г.; Знаковська, Є.А. (Proceedings of National Aviation University (archive), 2012)
In this article the upgraded mathematical model for identification of constellation of navigating satellites GPS, GLONASS and GALILEO is presented. This model may be used for more adequate aeronavigation means integrity definition.